IMPLEMENTASI PROGRAM IPTEK BAGI MASYARAKAT KELOMPOK INDUSTRI RUMAH JAMU TRADISIONAL - Abdullah Abdullah; Mariah Mariah (Jurnal Bisnis dan Kewirausahaan, 2016)
This article describes the results of the Science and Technology for Society (IbM) for training, coaching and mentoring to the Group of Traditional Herbal Medicine Industry Households in the village of Ujung Pandang Bulogading the District and Sub-District of Tallo Tallo Makassar. This activity aims to: (1) Improving the status and role of women in the field of traditional herbal medicine processing. (2) Achieving gender equality and justice so that they can also provide income for his family. (3). Improving the quality of the role and independence of the group of traditional herbal medicine. (4) Making of traditional herbal medicine business as a source of income for the women of the household. Outcomes achieved from this program are: (1) Increasing the quality and quantity of production. (2) the increased productivity of the business partners according to market needs. (3) Increasing this types of medicinal products. (4) Increased knowledge and skills of partner members in the process of production of herbal medicine. (5) Increased capacity and understanding of managing board of partners in business administration. (6) Increased attention Civitas academic STIE Nobel against the group of traditional herbal medicine as well as science and technology development activities.